Over 100-Year Preservation and Temporal Fluctuations of Cell Wall Polysaccharides in Marine Sediments - Salmeán, Armando A.; Willats, William George Tycho; Ribeiro, Sofia; Andersen, Thorbjørn Joest; Ellegaard, Marianne (Frontiers in Plant Science, 2022)
Polysaccharides constitute an important carbon pool in marine systems, but much is still unknown about the fate and degradation of these compounds. They derive partly from production in situ and in coastal areas are partly terrestrially derived, originating from freshwater run-off from land. Our aim in this paper was to test the applicability of high-throughput polysaccharide profiling for plant and algae cell-wall compounds in dated sediment cores from a coastal marine environment, to examine the preservation of cell-wall polysaccharides and explore their potential as proxies for temporal environmental changes. Preserved compounds and remains of organisms are routinely used as paleo-environmental proxies as the amount and composition of different compounds can provide insight into past environmental conditions, and novel means for reporting environmental change are highly sought.